Тричастинкові поля як метод опису баріонів у процесах розсіяння - Potiienko, O.S.; Sharph, I.V.; Chudak, N.O.; Zelentsova, T.M.; Neboga, G.G.; Merkotan, K.K. (Publishing house "Academperiodika", 2024)
A model of three-particle fields has been proposed to describe baryons in elastic and inelastic scattering processes. The model makes it possible to describe the confinement of quarks in a hadron and, simultaneously, the interaction of quarks in various hadrons, when the latter collide. Such an interaction is provided by the exchange of bound states between two gluons that are also in the confinement state.